An Analysis of Students’ Error in Using Cohesive Devices in Writing Analytical exposition text - aprida irmayana; Lollo Rosa Lubis (Jurnal Education and Development, 2018)
This research was done to investigate the students’ error in writing analytical exposition text at the Fourth Semester of Institut Pendidikan Tapanuli Selatan. The aim of this research were: 1) to find out the amount of errors made by the students, 2) to find out the most frequently error made by the students, 3) to find out the least frequently error made by the students. The writer used a descriptive qualitative method. The subjects of this research were 20 at fourth semester of Institut Pendidikan Tapanuli Selatan in Academic year 2018/2019. To collect data the writer used English writing essay test. The collected data was identified, classified, and analyzed based on the types of error using Dulay’s Theory (the surface strategy taxonomy). The result of the research shows that: 1) the total amount of error made by the students were 168 errors. They included misformation type (81=43.50%), addition type (49=26.30%), omission type (38=20.40%) and misordering type (18=9.70%). 2) the most frequently error made by the students was misformation type (81=43.50%, 3) the least frequently error made by the students was misordering type (18=9.70%).